Adaptive Q-Learning-Based Radio Resource Management Optimization in 5G and Beyond Heterogeneous-heterogeneous Networks: A Comprehensive Review - Abdulkadir, Abubakar; Kabir, Mahmoud T.; Abdulkareem, H. A.; Abdullahi, ZM (Darul Yasin Al Sys, 2025)
This paper reviews advanced radio resource management (RRM) optimization techniques in 5G and beyond heterogeneous-heterogeneous networks (Het-HetNets). Key innovations include fairness-aware models for mmWave 5G, machine learning (ML)-driven traffic management, and game-theoretic approaches for interference mitigation in Massive MIMO systems. Blockchain technology emerges as a promising tool for secure spectrum sharing, while deep learning enhances handover management and resource allocation. Hybrid frameworks, such as deep reinforcement learning and non-orthogonal multiple access, address energy efficiency and quality of service (QoS) challenges for IoT, autonomous vehicles, and smart cities. Despite these advancements, challenges like scalability, computational complexity, and data privacy persist. Q-learning-based adaptive RRM frameworks demonstrate potential for optimizing energy and spectral efficiency by addressing dynamic network conditions. The integration of ML with blockchain enables secure and decentralized RRM. Critical research gaps identified include scalability, real-time deployment, and interference management in ultra-dense networks. This review highlights the importance of scalable, efficient, and adaptive solutions to advance the telecommunications system.